2022
DOI: 10.1002/cre2.670
|View full text |Cite
|
Sign up to set email alerts
|

Thermal damage and excision time of micro and super pulsed diode lasers: A comparative ex vivo analysis

Abstract: Objectives The primary aim of this ex vivo study was to evaluate thermal damage and cutting efficiency of micro and super pulsed diode lasers. The secondary aim was to suggest a guideline to perform simple surgical excisions adequate for histopathological evaluation. Material and Methods Ten groups of 10 specimens of pig tongues were excised using a blade (G1), a micro pulsed (G2–G9), and a super pulsed diode (G10) lasers. Different output power, pulse duration, pulse interval, and duty cycle were tested. Quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In this regard, Fornaini et al have reported that in the pulsated laser, the stop between pulses protects the tissue from overheating due to thermal relaxation time. 11,13,18 Sindel et al reported that the minimal difference in the temperature rise between groups in two lasers comparison was between the power outputs of Er, Cr: YSGG lasers (2780 nm) and the lowest rise in temperature was with 2.75 W of the Er, Cr: YSGG laser. 12 In this study, it was also noticed that the mean of G3 of Er, Cr: YSGG was lower in the temperature rise than G1 and G2 of the diode laser.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, Fornaini et al have reported that in the pulsated laser, the stop between pulses protects the tissue from overheating due to thermal relaxation time. 11,13,18 Sindel et al reported that the minimal difference in the temperature rise between groups in two lasers comparison was between the power outputs of Er, Cr: YSGG lasers (2780 nm) and the lowest rise in temperature was with 2.75 W of the Er, Cr: YSGG laser. 12 In this study, it was also noticed that the mean of G3 of Er, Cr: YSGG was lower in the temperature rise than G1 and G2 of the diode laser.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is crucial for oral pathology to minimize peri-incisional heat injury. 5,[9][10][11] The conversion of light energy into heat due to the photothermal effect of laser tissue interaction may cause a rise in temperature and then damage to the surrounding area of the incision on both vertical and horizontal plane, 12 which will have an effect on the histopathological diagnosis and the healing of the tissue.…”
Section: Introductionmentioning
confidence: 99%